Penegakan Hukum Terhadap Eksistensi Tindak Pidana Pemalsuan Identitas di Era Digital (LEGAL DIALOGICA, 2025)
This research aims to determine and analyze the application of material criminal law to criminal acts of identity fraud in the digital era and criminal law enforcement in protecting individual personal data based on the Criminal Code (KUHP). This research uses Normative Empirical legal research methods. The results of this research show that (1) The application of material criminal law to criminal acts of identity fraud in the digital era has shown an unpreparedness in dealing with crimes that are developing along with the rapid progress of information and communication technology. Factors such as the public's lack of legal awareness, as well as the incompatibility between existing regulations and technological developments, influence the effectiveness of the application of material criminal law to the crime of digital identity fraud. (2) the effectiveness of criminal law enforcement in protecting individual personal data based on the Criminal Code (KUHP) is still considered less than optimal. The regulations regarding personal data protection in the Criminal Code are not specific enough considering the rapid development of information technology which affects the way personal data is collected, processed and distributed.Abstrak:Penelitian ini bertujuan untuk mengetahui dan menganalisis penerapan hukum pidana materil terhadap tindak pidana pemalsuan identitas di era digital dan penegakan hukum pidana dalam melindungi data pribadi individu berdasarkan Kitab Undang-Undang Hukum Pidana (KUHP). Penelitian ini menggunakan metode penelitian hukum Normatif Empiris. Hasil penelitian ini menunjukan bahwa (1) Penerapan hukum pidana materil terhadap tindak pidana pemalsuan identitas di era digital telah menunjukkan adanya ketidaksiapan dalam mengatasi kejahatan yang berkembang seiring dengan pesatnya kemajuan teknologi informasi dan komunikasi. Faktor seperti kurangnya kesadaran hukum masyarakat, serta ketidaksesuaian antara regulasi yang ada dan perkembangan teknologi, mempengaruhi efektivitas penerapan hukum pidana materil terhadap kejahatan pemalsuan identitas digital. (2) efektivitas penegakan hukum pidana dalam melindungi data pribadi individu berdasarkan Kitab Undang-Undang Hukum Pidana (KUHP) masih terbilang kurang optimal. Pengaturan tentang perlindungan data pribadi dalam KUHP tidak cukup spesifik mengingat pesatnya perkembangan teknologi informasi yang mempengaruhi cara data pribadi dikumpulkan, diproses, dan disebarkan.